Longitudinal Follow-Up on Cardiopulmonary Exercise Capacity Related to Cardio-Metabolic Risk Factors in Children With Renal Transplants - Westphal Ladfors, Susanne; Bergdahl, Ebba; Hermannsson, Oli; Kristjansson, Julius; Linnér, Tina; Brandström, Per; Hansson, Sverker; Dangardt, Frida (Frontiers in Sports and Active Living, 2021)
Background: Children with chronic kidney disease, including those treated with kidney transplantation (KT), have an increased risk of cardiovascular disease. The aim of this study was to examine the cardiopulmonary exercise capacity after KT compared to matched controls, to relate the results to physical activity, blood pressure and biochemical findings and to follow exercise capacity over time. Methods: Patients with KT (n = 38, age 7.7–18 years), with a mean time from transplantation of 3.7 years (0.9–13.0) and mean time in dialysis 0.8 years, were examined at inclusion and annually for up to three years. Healthy controls (n = 17, age 7.3–18.6 years) were examined once. All subjects underwent a cardiopulmonary exercise test, resting blood pressure measurement, anthropometry and activity assessment. Patients also underwent echocardiography, dual-energy X-ray absorptiometry (DXA), 24-h ambulatory BP measurements (ABPM), assessment of glomerular filtration rate (GFR) and blood sampling annually. Results: As compared to healthy controls, KT patients showed decreased exercise capacity measured both as VO2peak (34.5 vs. 43.9 ml/kg/min, p < 0.001) and maximal load (2.6 vs. 3.5 W/kg, p < 0.0001), similarly as when results were converted to z-scores. No significant difference was found in weight, but the KT patients were shorter and had higher BMI z-score than controls, as well as increased resting SBP and DBP z-scores. The patient or parent reported physical activity was significantly lower in the KT group compared to controls (p < 0.001) In the combined group, the major determinants for exercise capacity z-scores were activity score and BMI z-score (β = 0.79, p < 0.0001 and β = −0.38, p = 0.007, respectively). Within the KT group, low exercise capacity was associated with high fat mass index (FMI), low activity score, low GFR and high blood lipids. In the multivariate analysis FMI and low GFR remained predictors of low exercise capacity. The longitudinal data for the KT patients showed no change in exercise capacity z-scores over time. Conclusion: Patients with KT showed decreased exercise capacity and increased BP as compared to healthy controls. Exercise capacity was associated to GFR, physical activity, FMI and blood lipids. It did not improve during follow-up.